2005
DOI: 10.1002/j.0022-0337.2005.69.5.tb03942.x
|View full text |Cite
|
Sign up to set email alerts
|

The Crowning Achievement: Getting to the Root of the Problem

Abstract: An ideal goal of oral-craniofacial dental reconstructive therapy is to establish treatment modalities that predictably restore functional tissues. One major area of focus has been in the area of dental materials with marked improvements in the design of materials used to restore teeth/periodontium/bone lost as a consequence of disease or disorders. With advances in understanding the cell and molecular controls for development and regeneration of tooth structures, it is now possible to consider therapies that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…Yet, it is widely believed that an extension of the inner and outer dental epithelia in the tooth cervical loop, namely the Hertwig’s epithelial root sheath, probably initiates differentiation of odontoblasts from the peripheral mesenchymal cells followed by tooth root formation. Interestingly, there is no report of successful attempts to induce tooth root formation either in vitro or in vivo , although significant progress has been achieved in regenerating the tooth crown (34). In the present study, we demonstrated that osteoclasts play an essential role in root formation.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it is widely believed that an extension of the inner and outer dental epithelia in the tooth cervical loop, namely the Hertwig’s epithelial root sheath, probably initiates differentiation of odontoblasts from the peripheral mesenchymal cells followed by tooth root formation. Interestingly, there is no report of successful attempts to induce tooth root formation either in vitro or in vivo , although significant progress has been achieved in regenerating the tooth crown (34). In the present study, we demonstrated that osteoclasts play an essential role in root formation.…”
Section: Discussionmentioning
confidence: 99%
“…The periodontium can be defined as ‘an intricate mosaic of cells and proteins that is primarily responsible for the attachment of teeth in the oral cavity’ (144). Several excellent reviews have been published describing the embryonic lineage of the principal periodontal tissues (cementum, periodontal ligament, gingiva and alveolar bone), as well as the cells and extracellular matrix components of the periodontium (10, 13, 14, 21, 19, 46, 45, 51, 71, 80, 82, 144, 158, 185, 186, 193, 212, 214, 243, 244, 245).…”
Section: Development Of the Periodontiummentioning
confidence: 99%
“…Epithelial–mesenchymal interactions between odontogenic epithelium and ectomesenchymal cells typically include the dental epithelium and ectomesenchymal cells during the initial stage of tooth development, ameloblasts and odontoblasts during the crown‐formation process, and HERS and cementoblasts during root formation (20). In the present study, dental follicle cells and cementoblasts induced the apoptosis of ameloblasts and HERS/ERM cells.…”
Section: Discussionmentioning
confidence: 99%